Antifungal activity and hair growth stimulation of purple sweet potato leaf fraction (Ipomoea batatas (L.) Lamk) and its molecular mechanism through androgen receptor inhibition - Fery Indradewi Armadany; Iyan Sopyan; Resmi Mustarichie; Ruslin; Arfan (Pensoft Publishers, 2024)
Alopecia presented a global challenge, spurring the search for new treatments. This study evaluated Ipomoea batatas leaf extracts for their ability to stimulate hair growth and inhibit Malassezia furfur. Secondary metabolites were identified and assessed for their potential to inhibit androgen receptors (AR) via LC-MS/MS and in silico analysis. The hair tonic formulation was optimized using a D-optimal mixture design to improve physicochemical properties. The plant's extracts and fractions exhibited strong antifungal activity against M. furfur and significant hair growth stimulation compared to minoxidil. In silico analysis identified pyropheophorbide A, methyl-Pyropheophorbide A, hyperoside, and quercetin with superior affinity and stability in interacting with AR. The optimized formulation included 96% ethanol, propylene glycol, and Tween 80 to enhance hair tonic properties. I. batatas leaves showed promising potential in treating alopecia through hair growth stimulation, antifungal activity, and potential inhibition of AR. These findings opened avenues for further research and development in alopecia therapeutics.